hat's Why I Never Learned English From Indonesian Teachers: Investigating Native-Speakerism in Youtube Video Comments - Kaldina, Vindi; Darmawan, I Nyoman Pasek (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractThis study aims to examine the extent to which native-speakerism (NS) is embedded in the comments responding to a YouTube video entitled â€œSalah Kursus Bahasa Inggris?- Seleb Englishâ€ by a YouTuber named Sacha Stevenson. The researchers believe that native-speakerism, an ideology that creates a power imbalance favoring native speakers of English over nonnative speakers of English, is present in the video, in which the content creator scrutinizes Indonesian peopleâ€™s English accents. However, this paper focuses on the comments responding to the video, since they can show to what extent NS is adopted by EFL speakers/learners in Indonesia. The data was retrieved using YouTube Data API and Python programming language, sorted using Microsoft Excel, and categorized by applying three reading steps into four levels which spans from 0 (no indication of native speakerism) to 3 (strong indication of native speakerism). The findings are presented descriptively and analyzed within the theoretical framework on NS.Â The results suggest that NS is present in the observed comments on all three levels, which suggests how deeply embedded the NS ideology within the community of Indonesian English language learners and speakers. Suggestions on how to counter this ideology are presented in conclusion.Keywords: native-speakerism,Â youtube comments,Â english accent.AbstrakÂ Penelitian ini bertujuan untuk mengamati sejauh mana native-speakerism (NS) terkandung dalam komentar tanggapan pada video YouTube berjudul